Oxidative stress and endometriosis: review of the literature - L. V. Adamyan; M. M. Sonova; K. N. Arslanyan; O. N. Loginova; E. I. Kharchenko (Лечащий Врач, 2021)
Reactive oxygen forms (ROF) play an important role in modulating many physiological functions of the reproductive system, including the formation of endometriosis, are involved in the pathogenesis of infertility; There is a fine balance between ROF and antioxidants in the female reproductive process, which supports redox homeostasis. Oxidative stress occurs under conditions where the balance between ROF production and antioxidant protection is disturbed, and this may be due either to insufficient antioxidant protection or to excessive ROF production. Various data confirm the role of oxidative stress in the development and progression of endometriosis. This observation may open the way to assessment of therapeutic approaches aimed at correcting oxidative imbalance: the status of oxidative stress may be the key to treatment and, ultimately, to the prevention of endometriosis. In particular, in the future, clinical trials will help to better clarify the effectiveness of antioxidants as a potential therapy for endometriosis.